Systematic Review of Plant-Based Homeopathic Basic Research: An Update - Ücker, Annekathrin; Baumgartner, Stephan; Sokol, Anezka; Huber, Roman; Doesburg, Paul; Jäger, Tim (Homeopathy, 2018)
Background Plant-based test systems have been described as a useful tool for investigating possible effects of homeopathic preparations. The last reviews of this research field were published in 2009/2011. Due to recent developments in the field, an update is warranted. Publications on plant-based test systems were analysed with regard to publication quality, reproducibility and potential for further research.Methods A literature search was conducted in online databases and specific journals, including publications from 2008 to 2017 dealing with plant-based test systems in homeopathic basic research. To be included, they had to contain statistical analysis and fulfil quality criteria according to a pre-defined manuscript information score (MIS). Publications scoring at least 5 points (maximum 10 points) were assumed to be adequate. They were analysed for the use of adequate controls, outcome and reproducibility.Results Seventy-four publications on plant-based test systems were found. Thirty-nine publications were either abstracts or proceedings of conferences and were excluded. From the remaining 35 publications, 26 reached a score of 5 or higher in the MIS. Adequate controls were used in 13 of these publications. All of them described specific effects of homeopathic preparations. The publication quality still varied: a substantial number of publications (23%) did not adequately document the methods used. Four reported on replication trials. One replication trial found effects of homeopathic preparations comparable to the original study. Three replication trials failed to confirm the original study but identified possible external influencing factors. Five publications described novel plant-based test systems. Eight trials used systematic negative control experiments to document test system stability.Conclusions Regarding research design, future trials should implement adequate controls to identify specific effects of homeopathic preparations and include systematic negative control experiments. Further external and internal replication trials, and control of influencing factors, are needed to verify results. Standardised test systems should be developed.
Keywords: homeopathy; basic research; plant-based test systems; review